DO WE HAVE A CONSENSUS TO APPLY MODEL-BASED AMINOGLYCOSIDE THERAPY: A REVIEW OF POPULATION PHARMACOKINETIC MODELS. Issue 1 (14th December 2015) - Hao, Guo-Xiang; Teng, Sophie; Jacqz-Aigrain, Evelyne; Zhao, Wei
Abstract : Background and Objective: Aminoglycosides remain the standard antibiotic therapy for Gram-negative infections in both adults and children. The pharmacokinetic modeling approach has been widely used to evaluate aminoglycosides therapy. The aim of the present study is to review the published population pharmacokinetic models of commonly used aminoglycosides (gentamycin, amikacin and tobramycin), in order to determine if there was a consensus to apply model-based personalized aminoglycoside therapy in routine clinical practice. Methods: The bibliographic search was performed electronically using PubMed on 30th January 2015, following the search strategy: "((population Pharmacokinetics) OR (Pharmacokinetic modeling)) AND (gentamycin OR gentamicin OR amikacin OR tobramycin)". Results: A total of 49 articles were identified. Persistent variabilities exist in terms of structure model; typical pharmacokinetic parameters and identified covariates. Conclusion: A pharmacokinetic meta-analysis is required to evaluate the study-related factors influencing the pharmacokinetics of aminoglycosides. A clinical evaluation of pharmacokinetic model of aminoglycosides is required to demonstrate its clinical utility.